2005
DOI: 10.1037/0021-9010.90.6.1265
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Self-Efficacy in the Development of Entrepreneurial Intentions.

Abstract: The purpose of this study was to investigate the mediating role of self-efficacy in the development of students' intentions to become entrepreneurs. The authors used structural equation modeling with a sample of 265 master of business administration students across 5 universities to test their hypotheses. The results showed that the effects of perceived learning from entrepreneurship-related courses, previous entrepreneurial experience, and risk propensity on entrepreneurial intentions were fully mediated by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

161
1,920
11
95

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,137 publications
(2,323 citation statements)
references
References 34 publications
161
1,920
11
95
Order By: Relevance
“…Lastly, self-efficacy, innovativeness, and risk-taking are other important attributes. Arenius and Minniti found a strong role for confidence in one's skills as a factor distinguishing entrepreneurs from non-entrepreneurs [25] -a result confirmed by others [26], [27], [28]. Chen et al further specified entrepreneurial selfefficacy (ESE) into five sub-factors: marketing, innovation, management, risk-taking and financial control or self-efficacy [7].…”
Section: Entrepreneurship Literaturementioning
confidence: 90%
“…Lastly, self-efficacy, innovativeness, and risk-taking are other important attributes. Arenius and Minniti found a strong role for confidence in one's skills as a factor distinguishing entrepreneurs from non-entrepreneurs [25] -a result confirmed by others [26], [27], [28]. Chen et al further specified entrepreneurial selfefficacy (ESE) into five sub-factors: marketing, innovation, management, risk-taking and financial control or self-efficacy [7].…”
Section: Entrepreneurship Literaturementioning
confidence: 90%
“…Although early mixed findings in the entrepreneurship literature led scholars to shy away from research concerning personality and individual differences (Gartner, 1989;Low and MacMillan, 1988), recent research agrees that certain characteristics associated with resilience are common among nascent entrepreneurs (Brandstätter, 2011). Indeed, when it comes to understanding traits of typical nascent entrepreneurs, strong support has been found for individual differences such as achievement motivation (Ciavarella et al, 2004;Collins, Hanges and Locke, 2004;McClelland, 1961McClelland, , 1965, risk-propensity (Begley and Boyd, 1987;Miner and Raju, 2004;Stewart andRoth, 2001, 2004;Xu and Ruef, 2004;Zhao, Seibert and Lumpkin 2010), optimism (Arabsheibani et al, 2000;Cassar, 2009;Cooper, Woo and Dunkelburg, 1988;Hayward et al, 2010), self-efficacy (Chen, Greene and Crick, 1998;Chen, Gully and Eden, 2001;Zhao, Seibert and Hills, 2005), and social competence (Baron, 2000;Baron and Markman, 2003). Recognising this, entrepreneurship scholars and practitioners argue and find evidence suggesting that characteristics related to resilience play important roles in implementing entrepreneurial intentions, especially amidst adverse conditions and environments (Bullough and Renko, 2013;Bullough, Renko and Myatt, 2014;Krueger, Schulte and Stamp, 2008).…”
Section: Protective Factors and Resiliencementioning
confidence: 99%
“…In terms of entrepreneurship, entrepreneurial self-efficacy denotes one's belief that he or she is able to perform the tasks involved in starting and successfully managing a venture (Chen et al 1998). Indeed, researchers have found that entrepreneurial self-efficacy is positively related to the intention to act entrepreneurially (Zhao et al 2005;Zhao et al 2010) and to entrepreneurial action (Boyd and Vozikis 1994).…”
Section: Entrepreneurial Self-efficacymentioning
confidence: 99%
“…During the recent revival of studies on entrepreneurs' personal characteristics, scholars have gone past looking for "trans-situational consistency in personality traits" (Shaver and Scott 2002) and have begun exploring deeper models of individual characteristics, motivation, cognition, and behavior (e.g., Baron 2004;Baum and Locke 2004;Baum et al 2001;Busenitz and Barney 1997;Mitchell et al 2004;Rauch and Frese 2007;Zhao et al 2005). Take, for example, Baum et al (2001) and Baum and Locke (2004) who showed individual characteristics such as tenacity and passion do not have a direct association with new firm growth but that these variables are associated with growth-related motivation.…”
Section: Individual Values and Entrepreneurial Motivationmentioning
confidence: 99%
See 1 more Smart Citation